2016
DOI: 10.1177/1359105315603476
|View full text |Cite
|
Sign up to set email alerts
|

‘Drinking with respect’: Drinking constructions of men who live in a Cape Winelands farm community in South Africa

Abstract: This article aims to provide a community-specific understanding of a subgroup of South African men who exhibit particularly high rates of hazardous alcohol consumption. Adopting a social constructionist framework, we interviewed 13 Cape Winelands men who lived on farms to explore their drinking constructions. We present three themes that shed light on problematic drinking in this group: (1) the notion of weekend binge-drinking as 'respectable' drinking, (2) drinking as shared activity that fulfils various psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(62 reference statements)
0
1
0
2
Order By: Relevance
“…Finally, the cravings results demonstrated that only alcohol-specific reward was significantly associated with cravings. In this sample, alcohol was consumed on average 30% of the past 14 days, with majority of drinking days occurring on weekends, which is common in South Africa (Lesch & Casper, 2017; Parry et al, 2005). Weekend drinking often happens in this setting because people get paid from work on Fridays and prior evidence shows that having money can be a trigger for substance use (Dobkin & Puller, 2007; Swartz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the cravings results demonstrated that only alcohol-specific reward was significantly associated with cravings. In this sample, alcohol was consumed on average 30% of the past 14 days, with majority of drinking days occurring on weekends, which is common in South Africa (Lesch & Casper, 2017; Parry et al, 2005). Weekend drinking often happens in this setting because people get paid from work on Fridays and prior evidence shows that having money can be a trigger for substance use (Dobkin & Puller, 2007; Swartz et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…15 Ekipe hitnih medicinskih pomoći imaju znatno više poziva oko dva sata noću i trostruko više poziva krajem meseca zbog konzumacije alkohola i zadobijenih povreda. 16 Ovo se objašnjava povećanom konzumacijom alkohola tokom vikenda 17,18 što sledstveno dovodi do nasilnog ponašanja. 19 Prema podacima iz ESTP, nasilje je zabeleženo već u adolescentnom uzrastu.…”
Section: Diskusijaunclassified
“…Em outros continentes, não é diferente: na África do Sul, o consumo abusivo de álcool entre homens é o maior problema psicossocial que o país enfrenta (Gossage et al, 2014), pois esse consumo é considerado como um ícone da perpetuação da hegemonia masculina no decorrer da história, sempre atrelado à socialização entre pares do mesmo sexo (Lesch, 2017).…”
Section: Apsunclassified